Direct growth of InAs/GaSb type II superlattice photodiodes on silicon substrates. Issue 1 (1st February 2018) - González Burguete, Claudia; Guo, Daqian; Jurczak, Pamela; Cui, Fan; Tang, Mingchu; Chen, Wei; Deng, Zhuo; Chen, Yaojiang; Gutiérrez, Marina; Chen, Baile; Liu, Huiyun; Wu, Jiang
Abstract : In this study, p‐i‐n InAs/GaSb type II superlattice photodiodes were directly grown on silicon substrates. The superlattice structures were grown monolithically on miscut Si substrates via a 10 nm AlSb nucleation layer. Interfacial misfit array technique was used to accommodate the large lattice mismatch between III‐Sb epi‐layers and Si. Atomic force microscopy and X‐ray diffraction measurements revealed degraded material quality of type II superlattices grown on Si, compared with the sample grown on GaAs. Photoluminescence characterisation indicates comparable optical properties with about 39% deduction of peak intensity. Dark current measurements were also used to study the electrical properties of the samples.